MANAGEMENT OF ACUTE ISCHEMIC STROKE IN PEDIATRIC PATIENTS: CLINICAL METHODS AND OUTCOMES - Edyta Szymańska,; Adrianna Maria Mikołajczyk,; Patryk Pustuła,; Anna Maria Pietrzak,; Julia Prabucka-Marciniak,; Joanna Kaszczewska,; Zuzanna Natalia Burkacka,; Kacper Konrad Kmieć,; Zofia Szypuła,; Wiktoria Garbacz,; Hanna Eve Feder, (International Journal of Innovative Technologies in Social Science, 2025)
Background: Acute ischemic stroke (AIS) in the pediatric population is a rare condition. Despite its severe outcomes—including long-term neurological deficits and mortality— diagnosis of pediatric AIS is often delayed. In contrast to adult AIS, evidence-based guidelines for the pediatric population are limited, primarily due to the absence of data from multicenter randomized clinical trials.Aim: This review aims to present a comprehensive overview of the treatment methods of AIS in children, focusing on thrombolysis, mechanical thrombectomy, and supportive neuroprotective strategies.  Material and Methods: An in-depth literature review was performed using PubMed, ScienceDirect, and Google Scholar, including keywords such as: “pediatric acute ischemic stroke”, “PAIS”, “acute ischemic stroke in children”, “acute ischemic stroke management”, “tenecteplase”, “thrombolysis in children”Results: Intravenous thrombolysis with alteplase (0.9 mg/kg) may be considered in children ≥2 years of age within 4.5 hours of symptom onset, although data are still limited due to poor patient enrollment in the Thrombolysis in Pediatric Stroke Study (TIPS). Mechanical thrombectomy may be effective, even beyond the 6-hour window, particularly in cases involving large-vessel occlusion. Neuroprotective measures—such as glucose, temperature, and blood pressure control—may contribute to improved outcomes. For secondary prevention, antiplatelet or anticoagulant therapy is recommended.Conclusions: Management of AIS in children still relies on extrapolated adult data. There is an urgent need for pediatric-specific clinical trials to establish evidence-based treatment protocols and guidelines. In the meantime, early diagnosis, reperfusion strategies, and supportive neuroprotective measures appear to be critical.